Econometric models for planning - Eduardo Garcia d'Acuña (CEPAL Review, 1990)
The use of models in planning is almost as old as formalized planning itself, initiated in Latin America in the 1960s. Planning models were developed and used at both government and international agency levels, generally as simple analytical structures derived from the Harrod-Domar growth equation.